Gas/liquid/liquid three‐phase flow patterns and bubble/droplet size laws in a double T‐junction microchannel. Issue 5 (17th February 2015) - Wang, Kai; Qin, Kang; Lu, Yangcheng; Luo, Guangsheng; Wang, Tao
<x xml:space="preserve">Abstract</x> The double T‐junction microchannel is a classical microstructured chemical device used to generate gas/liquid/liquid three‐phase microflows. An experimental study that focused on the three‐phase flow phenomena and bubble/droplet generation rules in a double T‐junction microchannel was introduced. Based on the published knowledge of gas/liquid and liquid/liquid two‐phase microflows, new flow patterns were carefully defined: bubble cutting flow, spontaneous break‐up and bubble cutting coupling flow, and bubble/droplet alternate break‐up flow. According to the classical correlations of bubble and droplet volumes and their generation frequency ratio, the operating criteria for creating different three‐phase flow patterns were established and a model for the dimensionless average bubble and droplet volumes in the three‐phase microflows was developed. These various three‐phase microflows have great application potential in material science and flow chemistry synthesis. © 2015 American Institute of Chemical Engineers AIChE J, 61: 1722–1734, 2015